Evaluasi CIPP Pelatihan Pemanfaatan Sosial Media Marketing untuk Keluarga Penerima Manfaat Pelaku Usaha Program Keluarga Harapan - Zaqiyah, Nurul; Khoirinka, Raina Putri; Desidin, Al Qaromah; Putri, Septiani; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Poverty is still a challenge that must be resolved. Currently, many government programs have attracted controversy in various levels of society, especially in the programs launched. PKH (Family Hope Program) is a poverty alleviation program that provides assistance to KPM (Beneficiary Families). The aim of this research is to determine the community's needs in utilizing the social assistance received so that it is distributed well. The method used in evaluating this program is evaluation using a qualitative approach which is very relevant for researching a program. With students as community drivers to make changes through a training program on the use of social media marketing for KPM PKH Business Actors, it is hoped that community needs will be met by utilizing social media to market products so that community opinion increases and the community is self-reliant and is not dependent on social assistance. This is an educational effort to change the mind, behavior, knowledge, abilities, capacity and quality of society. Keywords: Poverty, society, programs